2018
DOI: 10.1002/adfm.201800945
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature Absorption, Photoluminescence, and Lifetime of CsPbX3 (X = Cl, Br, I) Nanocrystals

Abstract: The absorption and photoluminescence, both steady-state and timeresolved, of CsPbX 3 (X = Cl, Br, I) nanocrystals are reported at temperatures ranging from 3 to 300 K. These measurements offer a unique window into the fundamental properties of this class of materials which is considered promising for light-emitting and detection devices. The bandgaps are shown to increase from low to high temperature, and none of the examined cesium-based perovskite nanocrystals exhibit a bandgap discontinuity in this temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

45
191
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(238 citation statements)
references
References 57 publications
(96 reference statements)
45
191
2
Order By: Relevance
“…Usually, a facile thermal treatment process (e.g., ≈90 °C) is necessary for obtaining high‐performance QD‐based optoelectronic devices. But, for perovskite QDs, such thermal annealing could obviously decrease the PL properties resulting from an increase of nonradiative recombination centers, perhaps, due to the loss of organic ligands on the surface of QDs . The PLQY of primal QD films decreased to 47% with a reduction of 20% after treated at 90 °C for 5 min.…”
Section: Summary Of the Materials And Device Performance Parameters Ofmentioning
confidence: 99%
“…Usually, a facile thermal treatment process (e.g., ≈90 °C) is necessary for obtaining high‐performance QD‐based optoelectronic devices. But, for perovskite QDs, such thermal annealing could obviously decrease the PL properties resulting from an increase of nonradiative recombination centers, perhaps, due to the loss of organic ligands on the surface of QDs . The PLQY of primal QD films decreased to 47% with a reduction of 20% after treated at 90 °C for 5 min.…”
Section: Summary Of the Materials And Device Performance Parameters Ofmentioning
confidence: 99%
“…Magnetoabsorption, temperature dependence of photoluminescence, and optical absorption as well as theoretical calculations have been applied to determine the exciton binding energies in hybrid and all‐inorganic perovskites. MAPbI 3 as the prototype of perovskites in photovoltaics has been mostly discussed in these studies.…”
Section: Excitons and Related Phenomena In Metal Halide Perovskitesmentioning
confidence: 99%
“…Along with the increased research on 2D perovskites, much attention has been paid to examining the exciton binding energies of perovskite nanostructures such as nanoplatelets, nanosheets, nanowires, nanocubes, and nanocrystals/quantum dots . To compare the excitonic properties of 3D bulk and nanostructure perovskites, Zhang et al reported an E b value of ≈375 meV for MAPbBr 3 quantum dots while ≈65 meV for the 3D counterpart .…”
Section: Excitons and Related Phenomena In Metal Halide Perovskitesmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen that the theoretically calculated E b values of CsPbCl 3 and CsPbBr 3 are greater than the thermal energy value at RT, which indicates that CsPbCl 3 and CsPbBr 3 are optically more favorable. In fact, the relative accuracy of theoretical calculations was confirmed by experimental temperature‐dependent absorption, optical absorption, and magnetoabsorption …”
Section: Crystal Structure and Optoelectronic Properties Of Perovskitmentioning
confidence: 78%